William Faulkner. - O'Connor, William Van, 1915-1966 (University of Minnesota pamphlets on American writers ;, 1964)
William Faulkner - American Writers 3 was first published in 1959. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.